2007
DOI: 10.1007/978-3-540-72586-2_88
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Parallel Tree Reductions on Distributed Memory Environments

Abstract: Abstract.A new approach for fast parallel reductions on trees over distributed memory environments is proposed. By employing serialized trees as the data representation, our algorithm has a communication-efficient BSP implementation regardless of the shapes of inputs. The prototype implementation supports its real efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Further investigation in this direction is for future work. Our experiments were carried on a shared-memory machine; thus, experiments on different settings including distributed memory environments as well as comparison with different implementations including that by Kakehi et al [6] are also left for the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation in this direction is for future work. Our experiments were carried on a shared-memory machine; thus, experiments on different settings including distributed memory environments as well as comparison with different implementations including that by Kakehi et al [6] are also left for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Kakehi et al [6] proposed a parallel tree contraction algorithm for rose trees, which is different from both the Shunt contraction algorithm and the m-bridge decomposition method. With their approach, it is assumed that the input is in an XML-like format.…”
Section: Related Workmentioning
confidence: 99%
“…Kakehi et al [13] showed a parallel tree reduction algorithm from the nodes in chunks. Based on the idea given by Kakehi et al, Emoto and Imachi [6] developed a parallel tree reduction algorithm on Hadoop, and Matsuzaki and Miyazaki [17] developed a parallel tree accumulation algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…We can consider the text representation of XML as an flattened tree. Parallel algorithms for these flattened trees were proposed by Sevilgen et al [28] and by Kakehi et al [16]. We place the intermediate results on the stack in these algorithms and these results are communicated among c 2014 Information Processing Society of Japan processors.…”
Section: Parallel Processing On Tree Structuresmentioning
confidence: 99%